Factors associated with knowledge and attitude on prevention of dengue fever among international postgraduate students in a Malaysian university - Ghebreab, Luam Ghebrehiwot; Zainuddin, Huda (Community Health Society Malaysia, 2018)
Background: Dengue fever is a continuing public health burden globally, including Malaysia. Dengue fever has also become a burden among students who migrate to dengue endemic countries. Method: This cross-sectional study aimed to determine the associated factors of knowledge and attitude on prevention of dengue infection among international postgraduate students in a university in Malaysia. Descriptive and analytic statistics were used to analyze the data collected through structured questionnaire. Chi-Square/Fisher’s exact test and binary logistic regression was used to analyze the association and the predictors respectively. Level of significance was set at P less than 0.05. Results: A total of 327 international students participated with 93.4% response rate. Most of the students were male (70.3%), single (51.1%) and Asians (52.3%) with median age of 32 (IQR 10). Most of the respondents showed good knowledge (69.7%) and positive attitude (51.4%) towards prevention of dengue. Predictors of knowledge were being a female (aOR = 2.236, P = 0.007), previous history of dengue infection (aOR = 12.751, P = 0.007), longer duration of stay in Malaysia (aOR = 2.005, P = 0.007) and high influence of mass media (aOR = 3.076, P = <0.001). Predictors of positive attitude were, older age (aOR = 1.718, P = 0.024), higher perceived influence of mass media (aOR = 2.236, P = 0.007) and living in dengue endemic country (aOR = 1.796, P = 0.031). Conclusion: Knowledge and attitude of international students on prevention of dengue fever should be strengthened. The mass media should be optimally utilized as an influential source of information and health education regarding dengue infection.